2019
DOI: 10.1002/capr.12279
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors affecting child and adolescent psychotherapists' and counsellors' decision‐making in clinical work with parents

Abstract: This study examined interventions with parents/carers in child and adolescent counselling and psychotherapy (CAP). The aim was to investigate clinicians' rationale behind their decision to work with parents and what types of interventions they use. Furthermore, the nature of clinicians' core training with regard to interventions with parents was investigated. The study used both quantitative data and qualitative textual data from an online survey of 110 CAP clinicians. There was significant agreement, regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…One was a misrecruited dyadic therapy intervention, in another, the parent attended and actively participated in sessions to help overcome remote‐working challenges, and the remaining two had minimal parent–therapist interaction. While this supports Jäderberg et al's (2019) findings around the diversity of ways child practitioners work with parents, it is somewhat surprising that half the sample had very limited ongoing contact given the high levels of parent work reported in Jäderberg et al's sample. The self‐referring recruitment method may have contributed to the variance, attracting participants at extremes of involvement and satisfaction, keen to tell their story.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…One was a misrecruited dyadic therapy intervention, in another, the parent attended and actively participated in sessions to help overcome remote‐working challenges, and the remaining two had minimal parent–therapist interaction. While this supports Jäderberg et al's (2019) findings around the diversity of ways child practitioners work with parents, it is somewhat surprising that half the sample had very limited ongoing contact given the high levels of parent work reported in Jäderberg et al's sample. The self‐referring recruitment method may have contributed to the variance, attracting participants at extremes of involvement and satisfaction, keen to tell their story.…”
Section: Discussionsupporting
confidence: 78%
“…Siskind (1997) suggests there has historically been systemic ambivalence and avoidance surrounding parent work, leaving practitioners feeling unsupported, resigned and burdened in their dealings with parents. This view is supported by a survey of child and adolescent practitioners (Jäderberg et al, 2019), which found that while the vast majority of practitioners worked with parents in some capacity (94.4%), only 58.8% felt competent in this area, with less than half feeling adequately prepared for this work by their training (44.8%), leaving them unsure when and whether to involve parents.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The child in turn reacts to the ambivalence of the parents by clinging on to his or her symptoms. Not all doctors are sufficiently trained to overcome such communication deadlocks (Jaderberg, Goss, & McBeath, 2019). The parents' desire to visit other clinics should be considered as a warning signal.…”
Section: Typical Risks and Conflicts Of Decisionmentioning
confidence: 99%
“…Perceived self‐competence (PSC) is the belief of an individual that they can apply these strengths (Lippe et al., 2020), with higher levels of PSC linked to increased subjective happiness (Li, 2015) and improved work–life balance (Fotiadis et al., 2019). Competence in counsellors tends to focus on their ability to counsel certain groups (Jäderberg et al., 2020; Wada et al., 2019).…”
Section: Introductionmentioning
confidence: 99%